E-Worksheet for Students Using Liveworksheet for Digestive System Material - Syahria Fardinelly Syafar; Adeng Slamet; Rahmi Susanti; Makmum Raharjo (Universitas Pendidikan Ganesha, 2024)
The current problem is that many learning activities still need to utilize media as a learning support tool. This research aims to develop Electronic Student Worksheets (E-LKPD) in junior high school (SMP) science learning in science learning. This type of development research uses the Hannafin and Peck development model, which consists of needs analysis, development, design, implementation stages, and Tessmer evaluation. The population in this study was all Class VIII students, totalling 30 people. The research subjects were experts, including learning material experts, language experts, and learning media experts. The methods used in collecting data in this research were observation, interviews, questionnaires and tests. Data collection instruments include questionnaires and test questions. The techniques used to analyze the data are qualitative and quantitative descriptive analysis and N-gain. The results of the research were that the assessment given by material experts was 86.67 (very valid), linguist experts 88.89 (very valid), and media experts 98.46% (very valid). The results of the practicality test show that the Electronic Student Worksheet (E-LKPD) in science learning is highly qualified. The results of the N-gain test show an increase in learning outcomes, and the medium category is obtained, so it is effective. It was concluded that E-LKPD using live worksheets as teaching materials can increase the value of students' learning outcomes. The implication of this research is that E-LKPD uses the live worksheet that was developed and can be used in learning.